Feasibility Analysis of Gill Net Capture Business in Pekan Tua Village, Kempas Sub-District, Indragiri Hilir District, Riau Province - Saputra, Aldiyan; Sofyani, Tince; Arief, Hazmi (Jurnal Perikanan dan Kelautan, 2024)
The success of the fishing business is determined by several factors, including the fishing ground, the fishing fleet (fishing boat), the skills of the fishermen (skill), and the fishing gear itself. In this case, fishing gear is the basic construction material that determines the purpose and efficiency of new fishing results advancing toward specifications. This study analyses the investment, production, income, and business feasibility of gill net fishing gear in Pekan Tua Village, Kempas District, Indragiri Hilir Regency, Riau Province. The research method used is the survey method. The type of data collected includes primary data and secondary data. The results of this study are as follows: 1) Total investment of IDR0,931,500 with fixed capital of IDR 40,750,000 and working capital of IDR 181,5000. 2) The average catch of gill net fishermen in Pekan Tua Village in a year in the peak season is 1,413.7 kg /year, in the medium season in a year 1416.9 kg/year, and in the lean season in a year 473.80 kg year. The total catch of fishermen per year is 3,116.36 kg /year. The average net income fishermen earn based on the peak season is IDR 31,796,127, and the medium season IDR 32,650,170. The lean season IDR 5,004,336 3) Revenue Cost of Ratio (RCR) obtained a value of 2.19, Financial Rate of Return (FRR) of 169.68%, and in the Payback Period of Capital (PPC) analysis obtained a result of 0,59 or 6 months. So, based on this feasibility analysis, the gill net fishing gear business in Pekan Tua Village follows existing criteria/provisions, and it can be concluded that this business is profitable and feasible to run.